2017
DOI: 10.1590/1519-6984.06316
|View full text |Cite
|
Sign up to set email alerts
|

Protein from Hevea brasiliensis “Hev b 13” latex attenuates systemic inflammatory response and lung lesions in rats with sepsis

Abstract: Sepsis induces a severe systemic inflammatory response that may result in multiple organ dysfunction and death. Studies using a protein derived from natural Hevea brasiliensis (rubber tree) latex, denominated Hev b 13, have demonstrated important anti-inflammatory effects, but no data have been published regarding its effects on sepsis. The aim of this study was to investigate the effects of Hev b 13 on the inflammatory response and lung lesions of septal rats. Male Wistar rats were submitted to cecal ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous studies associate the effect of the F1 protein with immune cells, which can regulate the expression of inflammatory cytokines [6870]. F1 administration was able to reduce levels of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and increase levels of interleukin-10 (IL-10) and interleukin-4 (IL-4) which in general contribute to an anti-inflammatory effect [6870]. Our results suggest that F1 protein may be associated with the regulation of growth factors, such as NGF and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies associate the effect of the F1 protein with immune cells, which can regulate the expression of inflammatory cytokines [6870]. F1 administration was able to reduce levels of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and increase levels of interleukin-10 (IL-10) and interleukin-4 (IL-4) which in general contribute to an anti-inflammatory effect [6870]. Our results suggest that F1 protein may be associated with the regulation of growth factors, such as NGF and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…46 Although the PPNL mechanism of action is still poorly understood, it is speculated that an interaction with immune cells might be at play, 57 as demonstrated in studies that found an anti-inflammatory response with an increase in IL-10 and a decrease in IL-1b expression after PPNL use. 3,4 Moreover, cardiac fibroblast studies suggested that IL-1b upregulation increases MMP-2 expression and that this activity may be regulated by the PKC-u, PKC-z, and NF-kB pathways. 64 Hence, when MMP-2 expression was reduced with IL-1b, an increase in collagen synthesis was found.…”
Section: Discussionmentioning
confidence: 99%
“…20 There is no consensus in the literature on the optimal treatment for Achilles tendon ruptures, but they can be treated either nonoperatively or operatively with open or percutaneous repairs; however, some studies indicate surgery as the best option, mainly for athletes. 14,35 The American Journal of Sports Medicine 2019;47 (4):901-914 DOI: 10.1177/0363546518822836 Ó 2019 The Author(s)…”
mentioning
confidence: 99%
“…The slides (n=8) were examined by an experienced pathologist blinded to the treatments, using a light microscope (Olympus Corp., Tokyo, Japan) at 200× magnification (100 fields per section). Lung tissue lesions were classified as described in a previous study [13].…”
Section: Methodsmentioning
confidence: 99%